(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The study determined the influence of innovative and future-ready university business education programme in building human capacity for emerging markets in South-East, Nigeria. Two research questions and two null hypotheses guided the study. The study adopted survey research design, and 142 business educators in public universities offering business education programme in the South-East was studied without sampling. A-16 item structured questionnaire face validated by three experts in the field of education was used for data collection. The reliability of the instrument calculated using Cronbach alpha formula yielded correlation coefficients of.85 and.79 for clusters B1 to B2 respectively with an overall value of.82 obtained. Mean, standard deviation and t-test were used for data analysis. Findings revealed that innovative business education programmes influenced the development of future-ready skills among university students; business educators strongly agree on ways to design curriculum to meet the human capital needs of emerging labour markets in South East Nigeria. Years of teaching experience was not a significant factor in this regard. Based on the findings of the study, the researcher concluded that the implementation of innovative business education curriculum is important in equipping university students with the tools they need to succeed in changing and dynamic labour markets. It was recommended that business educators should incorporate new technologies in teaching business education courses. This will ensure that business education students are adequately equipped with future-ready skills relevant to emerging labour markets